Volatilitas Harga Saham di Indonesia dan Malaysia - Kartika, Andi (Jurnal Ilmiah Aset, 2010)
Disintermediatior phenomena in financial market show that many people tend to invest in capital market more than in banking. Thatâ€™s happened, because the return on stock is profitable than banking interest rate. But, there is a big risk in capital market. Itâ€™s natural, financial market says that high risk high return, low risk low return. So, if we do not want to loss, we must have ability to analyze stock performance, specially volatility of stock. This research useed ARCH/GARCH Model to estimate volatility. The research showed that stock growth in 2007 â€“ 2009 tended to decrease for all index (JSX and KLCI). JSX and KLCI just had ARCH effect, so the index influenced volatility this time price index. The research also showed, that Î± value eâ€ 0,7 and sum of Î± and Î² almost one for all index (JSX and KLCI). That means, the volatility shock was persistent or the volatility was high and persistent.